The Degree of Practicing Creative Leadership by Academic Leaders at Jordanian Universities and Its Relationship to the Level of Teaching Performance - Zohair H. Al-Zoubi; Hytham M. Bany Issa; Fawwaz Y. Musallam (Education Sciences, 2023)
This study aimed to identify the degree to which academic leaders at official Jordanian universities practice creative leadership and its relationship to the level of teaching performance according to faculty members’ point of view. This study also aimed to identify if there are statistically significant differences in the degree of creative leadership and in the level of teaching performance due to the variables of faculty and years of experience. It also aimed to examine the correlation between creative leadership and teaching performance. A descriptive correlative approach was used in this study, and the study sample consisted of 362faculty members at Jordanian universities during the second semester of the academic year 2020/2021.This study found that the degree of practicing creative leadership by the academic leaders at the faculties of Jordanian universities was high, and it also showed that there were no statistically significant differences inthe degree of academic leaders’ practice of creative leadership at the faculties of Jordanian public universities due to the variables of faculty and years of experience. The level of teaching performance of faculty members at the faculties of Jordanian universities was also high, and there were no statistically significant differences in the level of teaching performance of faculty members. There was a positive relationship between the degree of practicing creative leadership and the level of teaching performance of faculty members at Jordanian universities. According to the results of this study, the researchers recommended that universities should adopt the concept of creative leadership because of its positive role in achieving the universities’ mission, vision, and objectives, and in motivating employees.